Persistence of the Sciatic Artery: A Case Report of a Combined (Complete and Incomplete) Type Causing Leg Ischemia - Beatrice Cavallo Marincola; Alessandro Napoli; Michele Anzidei; Eugenio Marotta; Fabrizio Boni; Gaia Cartocci; Luca Bertaccini; Vincenzo Noce; Maria Antonietta Pacilé; Carlo Catalano (Case Reports in Vascular Medicine)
Persistent sciatic artery is a very uncommon embryologic vascular variant, with a prevalence of 0.05% based on angiographic studies. Two different types of this anomaly can occur, complete or incomplete, on the basis of the relationship between sciatic artery and femoral artery. Although many of these patients are asymptomatic, it may represent a threat to the viability of the lower extremity because of atherosclerotic degeneration resulting in aneurysmal dilatation, occlusive thrombosis, or embolic phenomena with distal complication. We present a case of a 64-year-old man with combined, complete and incomplete, type of persistent sciatic artery causing ischemic ulcer of the first toe.